Inhibiting or Contributing? How Global Liberal Forces Impact Climate Change Skepticism - Jessica Kim; Yasemin Nuhoğlu Soysal; Héctor Cebolla Boado; Laura Schimmöller (International Journal of Sociology, 2024)
Although climate change remains a top environmental threat, significant portions of the global population continue to exhibit climate change skepticism. Currently, an extensive literature identifies the micro-level determinants of climate skepticism, often manifesting as a form of populist “backlash” to the adverse effects of globalization. However, the potential of macro-level global cultural forces—particularly embeddedness in liberal world society—to counter such pushback is unclear. Using multilevel modeling to analyze International Social Survey Program data spanning 37 countries from 2000 to 2020, we find that in general, increased embeddedness is linked to reduced climate skepticism. However, when global liberal forces encounter anti-liberal undercurrents within nation-states, a situation we refer to as cultural dissonance, the impact of liberal world society on tempering skepticism varies. Embeddedness mitigates skepticism at the national level, particularly within authoritarian regimes, but not at the individual level, especially among right-wing individuals. Paradoxically, world society also heightens ideological polarization of individual worldviews on climate change. By illuminating the contradictory role of liberal world society, which simultaneously exacerbates and inhibits anti-liberal, populist attitudes about climate change, we advance existing work examining the post-liberal turn and holds promise for making sense of other issue domains where liberal perspectives are contested.
https://osf.io/jakwq/
Keywords: 300; Climate change skepticism; world society theory; cultural dissonance; anti-liberalism; ISSP